Perceptions of international school librarians on school library guidelines and standards: implications to international school libraries - Espiritu, Pauline B.
International schools have more unique institutional operations than local schools due to their exceptional nature. For this reason, their international school libraries are deemed autonomous regarding their processes, which involve the freedom to comply or not with school library guidelines and standards. Hence, this study centered on the perspectives of international school librarians on school library guidelines and standards and their implications for international school libraries. Specifically, on the impact of compliance or non-compliance to school library guidelines and standards and the library factors that influence them. This research also presents a qualitative study on the role of school library guidelines and standards in international school libraries. This role includes supporting the culture and character of the international school, advocating the library profession in the international school, upholding the reputation and prestige of the international school, encouraging linkages and networking activities with other international school libraries, providing effective library services for user satisfaction in the international school library, helping secure resources for the international school library, and recommending the acquisition of resources that represent diverse cultures and nationalities of the international school library patrons.